Analysis Of Virtual Product Marketing Strategies To Increase Customer Satisfaction (Case Study On Bukalapak Partners) - Artanti, Jessica; Agustini, Prima M.; Saptono, Arief; Kartika Hanum, Gilang; D.O., Regina (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2022)
This study aims to analyze the marketing strategy of Mitra Bukalapak in increasing customer satisfaction. In this study, the researcher uses a qualitative approach, which aims to find out what strategies are used by Bukalapak's internal partners to increase Customer Satisfaction. The data used for this research are primary data and secondary data. The results of the research analysis using in-depth interviews with the internal parties of Bukalapak Partners and Bukalapak Partners as triangulators where they transact using the Bukalapak Partner application as a place to transact. The segment of Mitra Bukalapak is for all levels, where the initial target is the klontong shop and the product positioning offered is virtual and wholesale products. From the 7P marketing mix implemented by Bukalapak Partners internally, there are several strategies that still need to be addressed, one of which is the price strategy because the price is still a sensitive issue, especially for buyers who are price-sensitive. However, there are also strategies that have been created and implemented that can accepted by Bukalapak Partners.